Global distribution of the He+ column density observed by Extreme Ultra Violet Imager on the International Space Station. Issue 7 (17th July 2017) - Hozumi, Yuta; Saito, Akinori; Yoshikawa, Ichiro; Yamazaki, Atsushi; Murakami, Go; Yoshioka, Kazuo; Chen, Chia‐Hung
Abstract: The global distribution of He + in the topside ionosphere was investigated using data of the He + resonant scattering emission at 30.4 nm obtained by the Extreme Ultra Violet Imager (EUVI) onboard the International Space Station. The optical observation by EUVI from the low‐Earth orbit provides He + column density data above the altitude of 400 km, presenting a unique opportunity to study the He + distribution with a different perspective from that of past studies using data from in situ measurements. We analyzed data taken in 2013 and elucidated, for the first time, the seasonal, longitudinal, and latitudinal variations of the He + column density in the dusk sector. It was found that the He + column density in the winter hemisphere was about twice that in the summer hemisphere. In the December solstice season, the magnitude of this hemispheric asymmetry was large (small) in the longitudinal sector where the geomagnetic declination is eastward (westward). In the June solstice season, this relationship between the He + distribution and the geomagnetic declination is reversed. In the equinox seasons, the He + column densities in the two hemispheres are comparable at most longitudes. The seasonal and longitudinal dependence of the hemispheric asymmetry of the He + distribution was attributed to the geomagnetic meridional neutral wind in the F region ionosphere. The neutral wind effect on the He + distribution was examined with an empirical neutral wind model, and it was confirmed that the transport of ions in the topside ionosphere is predominantly affected by the F region neutral wind and the geomagnetic configuration. Key Points: Global distribution of the He + column density in the evening topside ionosphere was elucidated statistically using the He + resonant scattering data set, observed from the low‐Earth orbit for the first time In the dusk sector, the He + column density in the winter hemisphere was about twice that in the summer hemisphere In the December solstice season, the magnitude of the hemispheric asymmetry was large (small) at longitudes where the geomagnetic declination is eastward (westward). In the June solstice season, this relationship between the He + distribution and the geomagnetic declination was opposite to that in the December solstice season